PENGARUHKECERDASAN EMOSIONAL TERHADAP KEMAMPUAN BERPIKIR MATEMATIS TINGKAT TINGGI - Siti Mutmainah (Jurnal Karya Pendidikan Matematika, 2018)
ABSTRACTThe aim of this study is to know the effect ofemotional quotienttowardhigh order mathematical thinking skill students of  Universitas Nahdlatul Ulama Lampung. This research is a quantitative research. The technique of collecting data is test in the form of essay test. The population of this study is allstudents of the sixth semester of Mathematics Education studyprogram inUniversitas Nahdlatul Ulama Lampung consisting of 60 students. The sample in this research is 40 students of Mathematics Education Study Program. The collecting data instrument is the instrument of high order mathematical thinking skillstudent and emotional quotient questionnaire instrument. The validity of the test instrument and questionnaire was performed by the validator, the test reliability was tested by the KR-20 formula and the questionnaire reliability was tested by the Alpha formula. The result of analysis concluded thatthe result of student highemotional quotient have betterhigh order mathematical thinking skill with student moderate and low emotional quotient, student moderate emotional quotient have betterhigh order mathematical thinking skill with student low emotional quotient.Key Words: Emotional Quotient, High Order Mathematical Thinking Skill